Application of digital image correlation in investigating the bond between FRP and masonry - Ghiassi, Bahman (2013)
Full characterization of the bond behavior between Fiber Reinforced Polymers (FRPs) and masonry in externally bonded reinforcement (EBR) technique is crucial at the design stage or structural performance prediction. In this regard, a full-field assessment technique seems to be valuable for an adequate characterization of the bond behavior. The digital image correlation (DIC) and feature tracking techniques have been used in this study for investigating the evolution of strains and deformation during uniaxial tensile tests and shear debonding tests in FRP-masonry systems. The results show that the DIC is a valuable technique for characterization of the bond behavior and investigating its three-dimensional aspects. The DIC was also found applicable for following the matrix crack development in Steel Reinforced Grout (SRG) specimens. Feature tracking method was used for monitoring the strains development on the steel fibers in SRG specimens during tensile tests.